Integration of Islamic Religious Education (PAI) with Pancasila in the Formation of Multicultural Character of Students in the Digital Era at SMP Muhammadiyah 03 Pacitan - Ermida, Ermida; Ismail, Ismail (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The integration of Islamic Religious Education (PAI) with Pancasila in shaping students' multicultural character in the digital era is a relevant topic in the context of multicultural globalization in Indonesia. Indonesian society faces various cultural, ethnic, and religious differences that require wise management to prevent social disintegration and to harness the innovative potential of multiculturalism. Education plays a crucial role in promoting peace, strengthening intercultural understanding, and creating an inclusive and harmonious society. This study aims to explore the planning of lessons integrating Islamic Religious Education with Pancasila in shaping a multicultural character at SMP Muhammadiyah 03 Pacitan. The research was conducted using a descriptive qualitative approach, focusing on the discussion of holistic and contextual character education in the school. The findings indicate that the integration of Islamic religious education with the values of Pancasila can serve as a strong foundation for building a peaceful and prosperous multicultural character. SMP Muhammadiyah 03 Pacitan has successfully implemented these integrative values within their curriculum, emphasizing respect for diversity and involving the roles of teachers and parents in the learning process. With the integration of Islamic religious education and Pancasila, the school has created an educational environment that promotes harmony and diversity in the ever-evolving digital era. This study contributes significantly to understanding how education can play a vital role in shaping tolerant and inclusive multicultural character amid globalization and digital technological advancements.